Identity of a Tilapia Pheromone Released by Dominant Males that Primes Females for Reproduction - Keller-Costa, Tina (2015)
Knowledge of the chemical identity and role of urinary pheromones in fish is scarce, yet it is necessary in order to understand the integration of multiple senses in adaptive responses and the evolution of chemical communication [1]. In nature, Mozambique tilapia (Oreochromis mossambicus) males form hierarchies, and females mate preferentially with dominant territorial males, which they visit in aggregations or leks [2]. Dominant males have thicker urinary bladder muscular walls than subordinates or females and store large volumes of urine, which they release at increased frequency in the presence of subordinate males or preovulatory, but not postspawned, females [3–5]. Females exposed to dominant-male urine augment their release of the oocyte maturation-inducing steroid 17α,20β-dihydroxypregn-4-en-3-one (17,20β-P) [6]. Here we isolate and identify a male Mozambique tilapia urinary sex pheromone as two epimeric (20α- and 20β-) pregnanetriol 3-glucuronates. We show that both males and females have high olfactory sensitivity to the two steroids, which cross-adapt upon stimulation. Females exposed to both steroids show a rapid, 10-fold increase in production of 17,20β-P. Thus, the identified urinary steroids prime the female endocrine system to accelerate oocyte maturation and possibly promote spawning synchrony. Tilapia are globally important as a food source but are also invasive species, with devastating impact on local freshwater ecosystems [7, 8]. Identifying the chemical cues that mediate reproduction may lead to the development of tools for population control [9–11].